The Aborigines' Protection Society: humanitarian imperialism in Australia, New Zealand, Fiji, Canada, South Africa, and the Congo, 1836 - 1909 - Heartfield, James (Columbia Univ. Press, 2011)
How the abolition of slavery changed Britain's empire -- The select committee on aborigines -- The Aborigines' Protection Society -- An empire to protect the aborigines -- The society and public opinion -- Conflict with the colonists -- Understanding the natives -- The Aborigines' Protection Society's work in the field -- Australia and the first aborigines' protectorate -- New Zealand and the Maoris -- Fiji and the Western Pacific -- The Indians of North America -- Colonising southern Africa -- For and against Leopold's Congo